Method for preparing modified clay mineral composite nanomaterial based on Click reaction and application

By introducing specific functional groups using the ‘Click’ reaction on the surface of clay mineral composite nanomaterials, the problem of single function of clay minerals in polymer composite solid electrolytes is solved, significantly improving its ionic conductivity and electrochemical stability, and broadening its application range.

CN119764617AActive Publication Date: 2025-04-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411913833.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Clay minerals have problems such as low surface chemical activity, poor dispersion and single function in polymer composite solid electrolytes, which limits their in-depth development and utilization.

Method used

The ‘Click’ reaction is used to accurately introduce specific functional groups on the surface of clay mineral composite nanomaterials. Through reaction with thiol compounds, different functional groups are successfully grafted to improve their physical and chemical properties.

Benefits of technology

It significantly improves the functionalization degree of clay mineral composite nanomaterials, enhances its ionic conductivity and electrochemical stability in polymer composite solid electrolytes, and broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for preparing a modified clay mineral composite nanomaterial based on a Click reaction and application of the modified clay mineral composite nanomaterial in preparation of a composite solid electrolyte. The preparation method comprises the following steps: firstly, carrying out hydrolytic condensation on vinyl silane on the surface of a clay mineral to prepare a vinyl silane modified clay mineral composite nano material; adding sulfydryl compounds containing different functional groups into the vinyl silane-clay mineral composite nanomaterial, grafting the different functional groups on the surface of the vinyl silane-clay mineral composite nanomaterial through a Click reaction to obtain a modified clay mineral composite nanomaterial, and finally preparing the composite solid electrolyte from the modified clay mineral composite nanomaterial. The method disclosed by the invention is simple and efficient, mild in operation condition and wide in applicability, and various functional groups can be accurately and efficiently grafted on the surface of the vinyl silane-clay mineral composite nano-material in a controllable manner, so that the surface performance of the vinyl silane-clay mineral composite nano-material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a modification method of a clay mineral composite nanomaterial, in particular to a method for preparing a modified clay mineral composite nanomaterial based on a "Click" reaction and an application thereof in preparing a composite solid electrolyte, belonging to the technical field of composite nanomaterials. Background Art

[0002] Clay minerals are a class of layered silicate materials that are widely present in nature. They have broad application prospects in catalysis, adsorption, and especially in the field of polymer composite solid electrolytes due to their abundant reserves, low cost, and excellent physical and chemical properties. The layered structure and high specific surface area of ​​clay minerals can provide abundant transmission channels for ion conduction, while their good thermal stability and mechanical strength help to improve the thermal stability and mechanical properties of polymer composite solid electrolytes. However, clay minerals often have some limitations in practical applications, such as low surface chemical activity, poor dispersibility, and single function. These defects limit their in-depth development and utilization in polymer composite solid electrolytes.

[0003] By modifying clay minerals, not only can they be given specific functions, but also their application range in polymer composite solid electrolytes can be broadened. At present, common methods for modifying clay minerals mainly include physical modification, chemical modification and composite modification. Physical modification usually changes the physical properties of clay minerals by mechanical crushing, heat treatment or ultrasonic dispersion, but this method has limited effect on improving the performance of clay minerals (CN202111655886.X, CN202311818828.3). Chemical modification includes intercalation reaction, acid treatment or organic molecule modification, which can give clay minerals new surface chemical activity and interface compatibility (CN202210379321.1, CN202410819724.2); for example, by intercalating lithium salts or other ion-conducting components, the ion conductivity of clay minerals in polymer composite solid electrolytes can be significantly improved. Composite modification is the preparation of multifunctional clay mineral composite nanomaterials by combining clay minerals with functional materials (such as metal oxides, polymers or carbon-based materials). Modified clay minerals can effectively improve their adsorption, ion exchange performance, as well as dispersibility and interface stability in polymer composite solid electrolytes (CN116124671A, CN117060009A, CN 116836570 A).

[0004] Although the above modification methods have made some progress in improving the performance and functionalization of clay minerals, there are still some technical bottlenecks that need to be overcome. For example, the introduction of functional components in the process of clay mineral modification often lacks precision, and it is difficult to use specific functional groups to regulate the physical and chemical properties of clay minerals (CN 116836570 A, Angew. Chem. Int. Ed. 2024, 63, e202400091). Different from the conventional clay mineral composite nanomaterial modification method, the present invention uses the "Click" reaction to precisely introduce specific functional groups on the surface of the modified clay mineral composite nanomaterial, giving it specific physical and chemical properties. The polymer composite solid electrolyte prepared with the composite nanomaterial as an additive can significantly improve its electrochemical properties such as ionic conductivity, and is expected to promote the widespread application of modified clay mineral composite nanomaterials in polymer composite solid electrolytes. Summary of the invention

[0005] The present invention aims to provide a method for preparing modified clay mineral composite nanomaterials based on "Click" reaction and its application in preparing composite solid electrolytes, to precisely modify the surface interface of clay mineral composite nanomaterials, and to prepare clay mineral composite nanomaterials with multiple specific functions. The present invention aims to precisely graft various functional groups onto the surface of clay mineral composite nanomaterials, significantly improve their functionalization degree, and thus broaden their application range.

[0006] 1. Preparation of modified vinylsilane@clay mineral composite nanomaterials by “Click” reaction (1) Preparation of vinylsilane@clay mineral composite nanomaterials The clay mineral is dispersed in a solvent and treated with ultrasound and stirring to form a uniform suspension. Subsequently, a nitrogen gas flow is introduced into the suspension to adjust the water content of the suspension to 50-400 ppm, and vinyl silane is added to modify the clay mineral through its hydrolysis condensation reaction (the hydrolysis condensation reaction is oscillated at 25-55 °C for 3-72 hours). After centrifugation, washing and drying, a vinyl silane@clay mineral composite nanomaterial is obtained, and the surface of the composite nanomaterial contains rich vinyl functional groups.

[0007] The clay mineral is at least one of diatomite, illite, montmorillonite, kaolinite and sepiolite, and the concentration of the clay mineral in the suspension is 0.5-30 mg / mL.

[0008] The solvent is ethanol, methanol, butyl ester, toluene, isopropanol, N -methyl- 2 - at least one of pyrrolidinone.

[0009] The vinyl silane is at least one of dimethylvinyl chlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane and vinyl trichlorosilane. The mass ratio of clay mineral to vinyl silane is 1:0.1 to 1:1. (2) Preparation of modified vinyl silane@clay mineral composite nanomaterials Vinylsilane@clay mineral composite nanomaterials were prepared by "Click" reaction. Vinylsilane@clay mineral composite nanomaterials were dispersed in solvent, azobisisobutyronitrile and thiol compounds were added, and the mixture was reacted at 20-80℃ for 2-48 h under nitrogen protection. Different functional groups were grafted on the surface of vinylsilane@clay mineral composite nanomaterials by "Click" reaction. Finally, modified vinylsilane@clay mineral composite nanomaterials were obtained by centrifugation, washing and drying.

[0010] The solvent is at least one of deionized water, methanol, butyl ester, toluene, isopropanol, and dimethylformamide. The thiol compound is propyl mercaptan, 3-mercaptopropionic acid, β -Mercaptoethanol, β - at least one of mercaptoethylamine.

[0011] The mass ratio of vinyl silane@clay mineral composite nanomaterial to azobisisobutyronitrile is 1:0.1~1:8; the mass ratio of vinyl silane@clay mineral composite nanomaterial to thiol compound is 1:0.1~1:5.

[0012] The synthesis mechanism of the present invention is as follows: based on the fact that the surface of the prepared vinylsilane@clay mineral composite nanomaterial contains abundant vinyl functional groups, different functional groups are successfully grafted onto the surface of the vinylsilane@clay mineral composite nanomaterial through a "Click" reaction with thiol compounds containing different functional groups.

[0013] Figure 1 The microscopic morphology of the vinylsilane@clay mineral composite nanomaterial in Example 2 is shown. The experimental results show that the surface of the vinylsilane@clay mineral prepared by this method is distributed with rice noodles, which have a length range of 100-1500nm and a diameter of about 10-70nm, and are evenly distributed on the surface of the clay mineral.

[0014] 2. Application of modified vinyl silane@clay mineral composite nanomaterials In order to reflect the excellent performance of the modified vinyl silane@clay mineral composite nanomaterial in the present invention, the modified vinyl silane@clay mineral composite nanomaterial in the present invention is used as a filler, dispersed in an organic solvent, and a polymer is added. After stirring at 20-80 ° C for 2-72 h, a uniform slurry is obtained. The slurry is coated on a polytetrafluoroethylene mold by a solution casting method, and dried and cured at 30-50 ° C for 12-72 h to obtain a modified vinyl silane@kaolinite composite nanomaterial / polymer composite solid electrolyte.

[0015] The organic solvent is dimethylformamide solution, anhydrous acetonitrile, N -methyl- 2 - one of pyrrolidone solution and tetrahydrofuran. The polymer is at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate; the mass ratio of the modified vinyl silane@clay mineral composite nanomaterial to the polymer is 1:0.1-1:10.

[0016] Ion transport: Figure 2 As shown in FIG. 2 , the polymer composite solid electrolyte prepared with the modified vinyl silane@clay mineral composite nanomaterial of Example 2 as an additive has a maximum ionic conductivity of 0.69×10 -3 Scm -1 , which is 1.2 times that of Example 1 and 2.8 times that of the comparative example.

[0017] Electrochemical stability: Figure 3 As shown, the experimental results show that the polymer composite solid electrolyte prepared with the modified vinyl silane@clay mineral composite nanomaterial of Example 2 as an additive has an electrochemical stability of 5.5 V, which is significantly better than the electrochemical stability of the polymer composite solid electrolyte (5.1 V) in the comparative example.

[0018] Beneficial effects of the present invention: The present invention provides an efficient, precise and controllable method, which can successfully graft a variety of functional groups onto the surface of vinylsilane@clay mineral composite nanomaterials. Through this method, not only the efficiency and precision of the grafting process are achieved, but also the controllable regulation of the grafting density and distribution is ensured. This technological breakthrough significantly improves the surface properties of composite nanomaterials, including surface activity, chemical stability and compatibility with other materials. In addition, the method is easy to operate, highly repeatable, and has good potential for industrial application, providing a new idea and technical support for the functionalization of composite nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the microscopic morphology of the vinylsilane@clay mineral composite nanomaterial in Example 2.

[0020] Figure 2 It is the ionic conductivity of the modified vinylsilane@clay mineral composite nanomaterial at different contents in the polymer composite solid electrolyte in the comparative example and Example 1 and Example 2.

[0021] Figure 3 This is the electrochemical stability of the comparative example and embodiment 2.

[0022] Figure 4 It is the lithium ion transfer number of comparative example, embodiment 2, embodiment 3, and embodiment 4.

[0023] Figure 5 The cycle stability of the lithium iron phosphate batteries assembled in the comparative example and embodiment 2. DETAILED DESCRIPTION

[0024] The present invention is further explained below with reference to specific embodiments.

[0025] Example 1 (1) Preparation of vinylsilane@kaolinite composite nanomaterials: 0.3 g of kaolinite was dispersed in 240 mL of N-methyl-2-pyrrolidone solution, ultrasonicated for 0.5 h, and then magnetically stirred for 12 h to form a uniform suspension. Subsequently, a nitrogen gas flow was introduced into the suspension to adjust the water content of the suspension to 180 ppm, and 1.5 g of vinyltrimethoxysilane was added to the suspension, shaken at room temperature for 24 h, and after the reaction was completed, the vinylsilane@clay mineral composite nanomaterial was obtained by centrifugation, washing and drying.

[0026] (2) Preparation of modified vinylsilane@kaolinite composite nanomaterials: Take 100 mL of ethanol solution, add 0.4 g of vinylsilane@kaolinite composite nanomaterials, 0.08 g of azobisisobutyronitrile and 0.2 g of propyl mercaptan, react at 50 °C under nitrogen protection for 8 h, rinse with ethanol solution 6 times, collect the precipitate by centrifugation, and dry it for later use.

[0027] (3) Preparation of modified vinyl silane@kaolinite composite nanomaterial / polyacrylonitrile composite solid electrolyte: 0.3 g of modified vinyl silane@kaolinite composite nanomaterial was dispersed in 30 mL of dimethylformamide solution, and 0.6 g of polyacrylonitrile was added. After magnetic stirring (speed of 600 RPM, stirring time of 12 h, temperature of 25°C), a uniform slurry was obtained. The slurry was coated on a polytetrafluoroethylene mold by solution casting method, and dried and cured at 30°C for 24 h to obtain a modified vinyl silane@kaolinite composite nanomaterial / polyacrylonitrile composite solid electrolyte. According to the test, the maximum ionic conductivity of the composite solid electrolyte at room temperature can reach 0.48×10 -3 Scm-1 ; The electrochemical stable voltage reaches 5.2 V.

[0028] Example 2 (1) Preparation of vinylsilane@montmorillonite composite nanomaterials: 0.1 g of montmorillonite was dispersed in 80 mL of toluene solution, ultrasonicated for 1 h, and then magnetically stirred for 12 h to form a uniform suspension. Subsequently, a nitrogen gas flow was introduced into the suspension to adjust the water content of the suspension to 200 ppm, and 1 g of vinyltrichlorosilane was added to the above suspension, shaken at room temperature for 12 h. After the reaction was completed, the suspension was centrifuged, washed and dried to obtain vinylsilane@clay mineral composite nanomaterials.

[0029] (2) Preparation of modified vinylsilane@montmorillonite composite nanomaterials: Take 50 mL of dimethylacetamide solution, add 0.5 g of vinylsilane@montmorillonite composite nanomaterials, 0.2 g of azobisisobutyronitrile and 0.5 g of 3-mercaptopropionic acid, and react at 70 °C under nitrogen protection for 12 h. Rinse with dimethylacetamide solution for 6 times and ethanol solution for 2 times. Collect the precipitate by centrifugation and dry it for later use.

[0030] (3) Preparation of modified vinylsilane@montmorillonite composite nanomaterial / polyethylene oxide composite solid electrolyte: 0.6 g of vinylsilane@modified montmorillonite composite nanomaterial was dispersed in 70 mL of anhydrous acetonitrile, and 0.6 g of polyethylene oxide was added. After magnetic stirring (speed of 600 RPM, stirring time of 12 h, temperature of 25 °C), a uniform slurry was obtained. The slurry was coated on a polytetrafluoroethylene mold by solution casting method, and dried and cured at 50 °C for 24 h to obtain a modified vinylsilane@montmorillonite composite nanomaterial / polyethylene oxide composite solid electrolyte. According to the test, the maximum ionic conductivity of the modified vinylsilane@montmorillonite composite nanomaterial / polyethylene oxide composite solid electrolyte at room temperature can reach 0.69×10 -3 Scm -1 The electrochemical stable voltage reaches 5.5 V, the lithium ion transfer number is 0.75, and the capacity retention rate of the assembled lithium iron phosphate battery reaches 95.5% after 500 cycles.

[0031] Example 3 (1) Preparation of vinylsilane@halloysite composite nanomaterials: 0.2 g of halloysite was dispersed in 120 mL of isopropanol solution, ultrasonicated for 1 h, and then magnetically stirred for 12 h to form a uniform suspension. Subsequently, a nitrogen gas flow was introduced into the suspension to adjust the water content of the suspension to 300 ppm, and 1.2 g of dimethylvinylchlorosilane was added to the above suspension, shaken at room temperature for 12 h. After the reaction was completed, the suspension was centrifuged, washed and dried to obtain vinylsilane@clay mineral composite nanomaterials.

[0032] (2) Preparation of modified vinylsilane@halloysite composite nanomaterials: Take 20 mL of methanol solution, add 0.3 g of vinylsilane@halloysite composite nanomaterials, 0.24 g of azobisisobutyronitrile and 0.4 g β -mercaptoethanol, react under nitrogen protection at 40 °C for 10 h, rinse with methanol solution 6 times, rinse with ethanol solution 2 times, collect the precipitate by centrifugation, and dry it for later use.

[0033] (3) Preparation of modified vinyl silane@halloysite composite nanomaterial / polyvinylidene fluoride composite solid electrolyte: 0.2 g of modified vinyl silane@halloysite composite nanomaterial was dispersed in 20 mL N -methyl- 2 -pyrrolidone solution, add 0.4 g of polyvinylidene fluoride, and obtain a uniform slurry after magnetic stirring (speed 600 RPM, stirring time 12 h, temperature 25°C). The slurry is coated on a polytetrafluoroethylene mold by solution casting method, and dried and cured at 50°C for 24 h to obtain a modified vinyl silane@halloysite composite nanomaterial / polyvinylidene fluoride composite solid electrolyte. According to the test, the maximum ionic conductivity of the modified vinyl silane@halloysite composite nanomaterial / polyvinylidene fluoride composite solid electrolyte at room temperature can reach 0.5×10 -3 S cm -1 ; The electrochemical stable voltage reaches 4.8 V, and the lithium ion transfer number is 0.65.

[0034] Example 4 (1) Preparation of vinylsilane@diatomite composite nanomaterials: 0.1 g of diatomite was dispersed in 180 mL of butyl ester solution, ultrasonicated for 1 h, and then magnetically stirred for 12 h to form a uniform suspension. Subsequently, a nitrogen gas flow was introduced into the suspension to adjust the water content of the suspension to 100 ppm, and 1 g of dimethylvinylchlorosilane was added to the suspension, shaken at room temperature for 12 h. After the reaction was completed, the suspension was centrifuged, washed and dried to obtain vinylsilane@clay mineral composite nanomaterials.

[0035] (2) Preparation of modified vinylsilane@diatomite composite nanomaterials: Take 40 mL of toluene solution, add 0.3 g of vinylsilane@diatomite composite nanomaterials, 0.15 g of azobisisobutyronitrile and 0.2 g β -Mercaptoethylamine, react under nitrogen protection at 80 °C for 6 h, rinse with toluene solution 6 times, wash with ethanol solution twice, collect the precipitate by centrifugation, and dry it for later use.

[0036] (3) Preparation of modified vinylsilane@diatomite composite nanomaterial / polymethyl methacrylate composite solid electrolyte: 0.9 g of modified vinylsilane@diatomite composite nanomaterial was dispersed in 50 mL of tetrahydrofuran, and 0.8 g of polymethyl methacrylate was added. After magnetic stirring (speed of 600 RPM, stirring time of 12 h, temperature of 25 °C), a uniform slurry was obtained. The slurry was coated on a polytetrafluoroethylene mold by solution casting method, and dried and cured at 40 °C for 12 h to obtain a modified vinylsilane@diatomite composite nanomaterial / polymethyl methacrylate composite solid electrolyte. According to the test, the maximum ionic conductivity of the modified vinylsilane@diatomite composite nanomaterial / polymethyl methacrylate composite solid electrolyte at room temperature can reach 0.3×10 -3 Scm -1 ; The electrochemical stable voltage reaches 4.6 V.

[0037] Comparative Example: Montmorillonite nanosheets: The thickness of montmorillonite nanosheets is about 1 nm and the average diameter is about 1 μm.

[0038] Application and performance: The polymer composite solid electrolyte was prepared by using montmorillonite nanosheets as an additive. The preparation method was the same as that in Example 1. After testing, the maximum ionic conductivity of the polymer composite solid electrolyte at 30 °C was 0.25×10 -3 Scm -1 , the electrochemical stability is 5.1 V, the lithium ion transfer number is 0.50, and the capacity retention rate of the assembled lithium iron phosphate battery is 78.1% after 500 cycles.

Claims

1. A method for preparing modified clay mineral composite nanomaterials based on "Click" reaction, comprising the following steps: (1) Preparation of vinylsilane@clay mineral composite nanomaterials: Clay minerals are dispersed in a solvent and treated by ultrasound and stirring to form a uniform suspension. Subsequently, a nitrogen gas flow is introduced into the suspension to adjust the water content of the suspension to 50-400 ppm, and vinylsilane is added to modify the clay minerals through its hydrolysis and condensation reaction. After centrifugation, washing and drying, vinylsilane@clay mineral composite nanomaterials are obtained. The hydrolysis and condensation reaction is carried out by shaking at 25-55 °C for 3-72 h. (2) The vinylsilane@clay mineral composite nanomaterial is dispersed in a solvent, and azobisisobutyronitrile and a thiol compound are added. The mixture is reacted at 20-80 °C for 2-48 h under nitrogen protection. Different functional groups are grafted on the surface of the vinylsilane@clay mineral composite nanomaterial using the "Click" reaction. Finally, the modified vinylsilane@clay mineral composite nanomaterial is obtained by centrifugation, washing, and drying.

2. The method for preparing modified clay mineral composite nanomaterials based on the "Click" reaction according to claim 1, characterized in that: In step (1), the clay mineral is at least one of diatomite, illite, montmorillonite, kaolinite and sepiolite, and the concentration of the clay mineral in the suspension is 0.5-30 mg / mL.

3. The method for preparing modified clay mineral composite nanomaterials based on the "Click" reaction according to claim 1, characterized in that: In step (1), the solvent is ethanol, methanol, butyl ester, toluene, isopropanol, N -methyl- 2 - at least one of pyrrolidinone.

4. The method for preparing modified clay mineral composite nanomaterials based on the "Click" reaction according to claim 1, characterized in that: In step (1), the vinyl silane is at least one of dimethylvinyl chlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, and vinyl trichlorosilane; and the mass ratio of the clay mineral to the vinyl silane is 1:0.1 to 1:

10.

5. The method for preparing modified clay mineral composite nanomaterials based on the "Click" reaction according to claim 1, characterized in that: In step (2), the solvent is at least one of deionized water, methanol, butyl ester, toluene, isopropanol, and dimethylformamide.

6. The method for preparing modified clay mineral composite nanomaterials based on "Click" reaction according to claim 1, characterized in that: In step (2), the thiol compound is propyl mercaptan, 3-mercaptopropionic acid, β -Mercaptoethanol, β - at least one of mercaptoethylamine.

7. The method for preparing modified clay mineral composite nanomaterials based on "Click" reaction according to claim 1, characterized in that: In step (2), the mass ratio of vinyl silane@clay mineral composite nanomaterial to azobisisobutyronitrile is 1:0.1-1:8; the mass ratio of vinyl silane@clay mineral composite nanomaterial to thiol compound is 1:0.1-1:

5.

8. Use of the modified clay mineral composite nanomaterial prepared by the method according to claim 1 in preparing a composite solid electrolyte, characterized in that: The modified vinyl silane@clay mineral composite nanomaterial is dispersed in an organic solvent, and a polymer is added. After stirring at 20-80 ℃ for 2-72 h, a uniform slurry is obtained. The slurry is coated on a polytetrafluoroethylene mold by a solution casting method, and dried and cured at 30-50 ℃ for 12-72 h to obtain a modified vinyl silane@kaolinite composite nanomaterial / polymer composite solid electrolyte.

9. The use of the modified clay mineral composite nanomaterial according to claim 8 in the preparation of a composite solid electrolyte, characterized in that: The organic solvent is dimethylformamide solution, anhydrous acetonitrile, N -methyl- 2 -One of pyrrolidone solution and tetrahydrofuran.

10. The use of the modified clay mineral composite nanomaterial according to claim 8 in the preparation of a composite solid electrolyte, characterized in that: The polymer is at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate; the mass ratio of the modified vinyl silane@clay mineral composite nanomaterial to the polymer is 1:0.5-1:10.

Citation Information

Patent Citations

  • Nanocrystallization treatment method for layered clay minerals

    CN114289133A

  • A method for preparing mesoporous materials based on clay minerals

    CN114804134B

  • Detection equipment and detection method for gas adsorption performance of clay mineral system

    CN116124671A

  • Clay mineral composite membrane material as well as preparation method and application thereof

    CN117060009A

  • Carbon-silicon oxide nano composite material based on clay minerals as well as preparation method and application of carbon-silicon oxide nano composite material

    CN117772131A